Economic Abuse as an Invisible Form of Domestic Violence: A Multicountry Review. (April 2020) - Postmus, Judy L.; Hoge, Gretchen L.; Breckenridge, Jan; Sharp-Jeffs, Nicola; Chung, Donna
The predominant perception of intimate partner violence (IPV) as constituting physical violence can still dominate, particularly in research and media reports, despite research documenting multiple forms of IPV including sexual violence occurring between intimate partners and various forms of psychological and emotional abuse. One frequently hidden or "invisible" form of abuse perpetrated within intimate partner relationships is economic abuse, also referred to as financial abuse in much of the literature. While the links between gendered economic insecurity and economic abuse are emerging, there remains a lack of consistency about definitions within the United States and globally, as there is no agreed upon index with which to measure economic abuse. As such, the purpose of this article is to review and analyze the global literature focused on either economic or financial abuse to determine how it is defined and what measures are used to capture its prevalence and impact. The 46 peer-reviewed articles that met all inclusion criteria for analysis came from a range of countries across six continents. Our review found that there is growing clarity and consistency of terminologies being used in these articles and found some consistency in the use of validated measures. Since this research is in its "infancy, " we need to have stronger collaborative efforts to use similar measures and terminology. Part of that collaborative effort is to consider how language and cultural differences may play a part in our understanding of economic abuse.